Pour une histoire comparée des intellectuels - Bock, Hans Manfred; Charle, Christophe; Granjon, Marie-Christine; Lamonde, Yvan; Löwy, Michael; Trebitsch, Michel; Zins, Max-Jean (Bruxelles : Editions Complexe, 1998)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: geschiedenis